Synthesis of Acyclic Marine Halogenated Natural Product Analogues from Myrcene - Krishna Mohan, S.; Meryala, Haribabu (Asian Journal of Chemistry, 2010)
Synthesis of acyclic halogenated marine natural products such as 1,8-dibromo-3,7-di(bromo methyl)-(Z)-2-octene (1), 1,6,7- tribromo-3-bromo methyl-7-methyl-(Z)-2-octene (2), 2,3-di(bromo methyl)-6-(1-bromo-1-methyl ethyl) tetrahydro-2H-3-pyranol (3), 2,6,7,8- tetrabromo-6-bromo methyl-2-methyl-3-octanol (4) was planned from myrcene in view of their good antitumour activity.